"Den Entwurf der Sowjetarchitekten Rosenfeld, Merson und Waldenberg für den neuen Sowjetpalast" - Valdenberg, ... (1932)
"Den Entwurf der Sowjetarchitekten Rosenfeld, Merson und Waldenberg für den neuen Sowjetpalast".